Safety and efficacy of 4‐phenylbut‐3‐en‐2‐one and benzophenone belonging to chemical group 21 when used as flavouring compounds for all animal species. (18th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of 4‐phenylbut‐3‐en‐2‐one [07.024] and benzophenone [07.032] belonging to chemical group 21, when used as feed flavourings for all animal species. They are currently authorised for use as flavours in food. The use of 4‐phenyl‐3‐butene‐2‐one [07.024] is safe at the proposed normal use levels of 1 mg/kg complete feed for all animal species. Benzophenone [07.032] is safe at the proposed normal use levels of 1 mg/kg complete feed for all animal species except chicken for fattening, laying hens and piglets, for which the calculated safe concentration in feed is 0.5 mg/kg. No safety concern would arise for the consumer from the use of 4‐phenyl‐3‐butene‐2‐one [07.024] and benzophenone [07.032] as feed flavourings. In the absence of studies to assess the safety for the user, the FEEDAP Panel cannot conclude on the safety for users when handling the additives. The use of 4‐phenyl‐3‐butene‐2‐one [07.024] and benzophenone [07.032] in animal feed at the maximum safe use level in feed is also considered safe for the environment. Since the compounds under assessment are used in food as flavourings and their function in feed is essentially the same as that in food, no further demonstration of efficacy is necessary.